2020
DOI: 10.1111/gcb.15410
|View full text |Cite
|
Sign up to set email alerts
|

Elevated atmospheric CO2 reduces yield‐scaled N2O fluxes from subtropical rice systems: Six site‐years field experiments

Abstract: Increasing levels of atmospheric CO2 are expected to enhance crop yields and alter soil greenhouse gas fluxes from rice paddies. While elevated CO2 (ECO2) effects on CH4 emissions from rice paddies have been studied in some detail, little is known how ECO2 might affect N2O fluxes or yield‐scaled emissions. Here, we report on a multi‐site, multi‐year in‐situ FACE (free‐air CO2 enrichment) study, aiming to determine N2O fluxes and crop yields from Chinese subtropical rice systems as affected by ECO2. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…As a result, Bt crops have been used to control a wider range of pests, such as Helicoverpa armigera (Hübner), Heliothis virescens , and Mythimna separata (Riddick et al, 1998 ; Chen F. J. et al, 2011 ; Chang et al, 2013 ). Meanwhile, human activities, specifically fossil fuel burning and land-use change, are rapidly increasing the level of carbon dioxide (CO 2 ) in the atmosphere (Yu and Chen, 2019 ; Yao et al, 2020 ). Specifically, it has been reported that the atmospheric CO 2 concentration increased from 288 to 405 ppm from 1800 to 2018 ( www.esrl.noaa.gov/gmd/ccgg/trends/ ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, Bt crops have been used to control a wider range of pests, such as Helicoverpa armigera (Hübner), Heliothis virescens , and Mythimna separata (Riddick et al, 1998 ; Chen F. J. et al, 2011 ; Chang et al, 2013 ). Meanwhile, human activities, specifically fossil fuel burning and land-use change, are rapidly increasing the level of carbon dioxide (CO 2 ) in the atmosphere (Yu and Chen, 2019 ; Yao et al, 2020 ). Specifically, it has been reported that the atmospheric CO 2 concentration increased from 288 to 405 ppm from 1800 to 2018 ( www.esrl.noaa.gov/gmd/ccgg/trends/ ).…”
Section: Introductionmentioning
confidence: 99%
“…Although Liu et al [5] considered that improving N availability mainly accounted for the enhanced N 2 O emission, the corresponding effect between N-limited natural ecosystems and N-rich agroecosystems was not distinguished. A recent report from a paddy rice field found that after 6 years of continuous observation eCO 2 , N 2 O emissions decreased obviously at an N application rate ≥ 150 kg N ha −1 , but remained unaffected at an N application rate ≤ 125 kg N ha −1 [16]. It should be noted that the paddy rice fields are periodically flooded, which does not occur in cropped upland; thus, it is uncertain whether the conclusions drawn from paddy rice fields are applicable to upland farming.…”
Section: Introductionmentioning
confidence: 97%
“…N 2 O emissions from croplands with N fertilization was responsible for 70% of global annual N 2 O emissions [11,12]. As N 2 O is a powerful greenhouse gas with 298-fold greater global warming potential than CO 2 [2] and is also involved in the destruction of stratospheric ozone [13], numerous previous research focused on measuring N 2 O emissions under different N application rates [14][15][16]. The effect of eCO 2 on N 2 O emissions is receiving more attention, since it can address our current knowledge gap about soil feedback of global warming.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations